At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
Are you able to isolate y in the equation `2x+y=11` ?
or you can isolate x in `x-3y=-12`
@unicornandmarshmellows if you really need help you need to stay on long enough to get the response and to participate. we are not here to do your work
yeah sorry i just hopped on really quick to post the question, (i wasn't just going to leave it hang) now im here !
also thanks @jim_thompson5910 ! i'll work it out from there :)
ok tell me what you get
am i on the right track?
why not solve for x in the first equation? it's much easier and doesn't involve fractions
oh okidoke then hold on for a second c:
so x = -12+3y or x = 3y - 12
now turn to the second equation 2x+y=11 replace each 'x' with either -12+3y or 3y-12 then solve for y
oh okidoke i see ! :)
can i try and see what i get and then run it to you for a quick run-through?
sure that sounds like a good plan
The part where you went from `2(-12+3y)` to `-24+3y` is incorrect. You forgot to distribute the 2 to EVERY term inside the parenthesis
oh ohh okidoke i see i'm going to fix that and brb!
wait i thought were supposed to only combine the like terms?
what do you mean?
like when you distribute the 2 throughout the equation, you would only combine the 2 and the 12 because they are like terms, while the 3 gets left out because its not just "3" its "3y"
you might be mixing up two different ideas? when you distribute, you multiply the outer 2 by each term inside 2 times -12 = -24 2 times 3y = 6y so `2(-12+3y)` becomes `-24+6y`
I think i might too lol and okidoke gotcha!
here's another way to look at it `2(-12+3y)` is really `(-12+3y)+(-12+3y)` similar to how `2x = x+x` so... (-12+3y)+(-12+3y) = (-12+(-12)) + (3y+3y) = -24 + 6y
i wish i could double medal, :) okidoke i hear you man c:
now i got x=3 and y=5!
Let's check that possible answer Checking equation 1 x-3y=-12 3-3*5=-12 ... replace x with 3 and replace y with 5 3 - 15=-12 -12=-12 ... true Checking equation 2 2x+y=11 2*3+5=11 ... replace x with 3 and replace y with 5 6+5=11 11 = 11 ... true both equations are true when (x,y) = (3,5) so the answer is confirmed to be true
awesome! thanks so much for the help man! :D i appreciate it !